2014
DOI: 10.1007/s13277-014-2667-5
|View full text |Cite
|
Sign up to set email alerts
|

Combine MEK inhibition with PI3K/mTOR inhibition exert inhibitory tumor growth effect on KRAS and PIK3CA mutation CRC xenografts due to reduced expression of VEGF and matrix metallopeptidase-9

Abstract: Although epidermal growth factor receptor (EGFR) monoclonal antibody (mAb) cetuximab are used widely to treat KRAS wild-type metastatic colorectal cancer (mCRC), patients become resistant by various mechanisms, including KRAS, BRAF, and PIK3CA mutations, thereafter relapsing. AZD6244 is a potent, selective, and orally available MEK1/2 inhibitor. In this study, we investigated the mechanisms of AZD6244 alone or with BEZ235, an orally available potent inhibitor of phosphatidylinositol 3-kinase (PI3K) and mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Interestingly, we found that the two drugs inhibit angiogenesis as a concomitant effect by suppressing VEGF secretion from tumor cells rather than a direct effect on vascular endothelial cells. Indeed combining MEK and mTOR inhibition exert antitumor effects on CRC xenografts due to reduced expression of VEGF [32]. Taken together, selumetinib enhances the antitumor activity of everolimus against RCC by synergistically inhibiting the expression of VEGF in addition to p-RPS6 and p-4E-BP1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the two drugs inhibit angiogenesis as a concomitant effect by suppressing VEGF secretion from tumor cells rather than a direct effect on vascular endothelial cells. Indeed combining MEK and mTOR inhibition exert antitumor effects on CRC xenografts due to reduced expression of VEGF [32]. Taken together, selumetinib enhances the antitumor activity of everolimus against RCC by synergistically inhibiting the expression of VEGF in addition to p-RPS6 and p-4E-BP1.…”
Section: Discussionmentioning
confidence: 99%
“…Dactolisib (BEZ235), a PI3K/mTOR dual inhibitor, is another recently developed molecule that has raised interest since its synergism with the oral MEK1/2 inhibitor selumetinib. The combination of these two targeted agents has resulted in tumor growth blockade in KRAS - and PIK3CA -mutated CRC xenografts, and the antitumor effect seemed to be associated with a downregulation of matrix metallopeptidase-9 (MMP-9) and angiogenic blockade [ 74 ]. These pre-clinical results suggest that dual blockade of the PI3K and MEK pathways may overcome resistance to MEK inhibitors, providing the rationale for performing clinical trials of this combination in patients.…”
Section: Emerging Target Molecules In Mcrc Treatmentmentioning
confidence: 99%
“…Combination treatment demonstrated enhanced reduction in tumor growth against CRC cell line and patient-derived tumor xenograft models as compared to either single agent regardless of KRAS or PI3K mutational status. Recently, E et al [ 46 ] also reported their results on the use of BEZ235 with selumetinib in HCT116 CRC cells harboring both KRAS and PIk3CA mutations. The combination treatment markedly enhanced their antitumor effects than either single agent alone.…”
Section: Pre-clinical Data On Dual Targeted Inhibition With Mekmentioning
confidence: 99%
“…The combination treatment markedly enhanced their antitumor effects than either single agent alone. The authors also reported a reduction in the phosphorylation level of ERK1/2 and AKT and in the expression of VEGF and matrix metallopeptidase-9 in tumor tissue [ 46 ].…”
Section: Pre-clinical Data On Dual Targeted Inhibition With Mekmentioning
confidence: 99%